The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.oprd.1c00312
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Synthesis of (R,R)-N,N-Dibenzyl-2-fluorocyclohexan-1-amine with CsF under Hydrogen Bonding Phase-Transfer Catalysis

Abstract: Hydrogen bonding phase-transfer catalysis offers a convenient solution to activate safe and economical metal alkali fluorides for enantioselective nucleophilic fluorination. Herein, we demonstrate the scalability of this protocol with the fluorination of 200 g of racemic trans-N,N-dibenzyl-2-bromocyclohexan-1-amine in a mechanically stirred 1 L glass reactor using 0.5 mol % of a bis-urea organocatalyst. In these experiments, full conversions were obtained for high mixing intensities (impeller average shear rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This metal-free organocatalyzed asymmetric fluorination has been successfully applied to the synthesis of a trans-2fluorocyclohexan-1-amine motif that is featured in several bioactive pharmaceutical molecules. 185 As shown in Scheme 60a, the enantioselective fluorination of racemic trans-N,Ndibenzyl-2-bromocyclohexan-1-amine 279 with CsF proceeded smoothly in the presence of N-alkyl bis-urea C34. The reaction gave β-fluoroamine [(R,R)-N,N-dibenzyl-2-fluorocyclohexan-1amine] 280 in 95% yield and 63% ee.…”
Section: Fluorinationmentioning
confidence: 99%
“…This metal-free organocatalyzed asymmetric fluorination has been successfully applied to the synthesis of a trans-2fluorocyclohexan-1-amine motif that is featured in several bioactive pharmaceutical molecules. 185 As shown in Scheme 60a, the enantioselective fluorination of racemic trans-N,Ndibenzyl-2-bromocyclohexan-1-amine 279 with CsF proceeded smoothly in the presence of N-alkyl bis-urea C34. The reaction gave β-fluoroamine [(R,R)-N,N-dibenzyl-2-fluorocyclohexan-1amine] 280 in 95% yield and 63% ee.…”
Section: Fluorinationmentioning
confidence: 99%
“…Furthermore, the protocol did not require dry conditions or pre-treatment of KF. We also developed a protocol to synthesize decagram quantities (>30 g) of bis-urea ( S )- 33b and ( S )- 33c , and subsequently employed the latter in the 200 g scale fluorination of 35f (this time with CsF) in a mechanical stirred 1 L glass reactor (Scheme C) . This substrate was selected because the corresponding deprotected β-fluoroamine is a valuable building block in drug discovery .…”
Section: Fluorination Via Solid–liquid Phase-transfer: Hydrogen Bondi...mentioning
confidence: 99%
“…In 2019, Gouverneur and co‐authors reported asymmetric synthesis of fluorinated dibenzylamines 86 involving the use of chiral hydrogen bonding phase‐transfer catalyst 85 (Scheme 30). [77] Albeit the method had moderate enantioselectivity, it could be used at up to 200 g (0.5 mol % of 85 , CsF as the fluoride source, n=2) since the er value of the product could be improved to 98 : 2 after a single recrystallization [78] …”
Section: Synthesis Of Monofluorinated Cycloalkyl Building Blocksmentioning
confidence: 99%
“…[77] Albeit the method had moderate enantioselectivity, it could be used at up to 200 g (0.5 mol % of 85, CsF as the fluoride source, n = 2) since the er value of the product could be improved to 98 : 2 after a single recrystallization. [78] Obviously, the reaction mechanism involved the formation of symmetric bicyclic aziridinium intermediates (see also below).…”
Section: Synthesis Of β-Fluorinated Cycloalkyl Building Blocksmentioning
confidence: 99%